The Dimensions of Expatriate Adjustment - Haslberger, Arno; Brewster, Chris; Hippler, Thomas (Human Resource Management, 2013)
AbstractA narrow and partial theoretical base has limited current concepts of expatriate adjustment and the research based upon them. This conceptual article explores one of the less theorized aspects of expatriate adjustment: the fact that it has multiple dimensions. We conceive of adjustment as a person‐environment relationship that takes place in the three dimensions of cognitions, feelings, and behaviors. Combining these elements takes us one step closer to a comprehensive and more realistic understanding of the nature of expatriate adjustment. We include suggestions for future research that follow from our reconceptualization.